Competitive anxiety level before and during competition among Malaysian athletes - Parnabas, Vincent. A; Mahamood, Yahaya (Universiti Putra Malaysia Press, 2010)
Anxiety is recognized as one of the main factors that reduces athletes’ performance in sports. In many research reviews, researchers have found that high levels of anxiety can have a deteriorating effect on athletes’ or teams’ performance. To date, however, there has been no attempt to examine competitive anxiety level as influenced by gender, levels of skills, and performance. The main aim of the study was to describe and compare the anxiety differences before and during competition among different categories of skills of athletes and genders. Data were collected from 902 athletes using a 27 item Competitive State Anxiety Inventory-2. The results showed that national level and male athletes obtained the lowest score on competitive state anxiety. Based on the current results, it is recommended that sport psychologists, sport counsellors, and coaches in Malaysia use the findings to design appropriate training programmes to help athletes acquire suitable coping strategies so as to reduce their state anxiety levels and enhance their performance.